2018
DOI: 10.1051/meca/2018011
|View full text |Cite
|
Sign up to set email alerts
|

A micromechanical scratch model to investigate wear mechanisms in UD-GFRP composites

Abstract: This study suggests a micromechanical approach to scrutinize the glass fiber reinforced polyester (GFRP) composite tribological behavior. A single indenter scratch test (SST) using spherical tip conical indenter was adopted. The 3D finite element (FE) model was developed into ABAQUS/Explicit commercial code. Both material behavior and damage of polyester matrix and glass fiber was modeled using the Johnson Cook behavior law. Nevertheless, the fiber/matrix interface behavior is described using the cohesive zone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Several statistical models can be used for the statistical analysis of composites. According to Slah et al [ 27 ], experimental approaches are insufficient when testing and analyzing the wear behavior of composite materials. Those authors suggested that this approach should be complemented with FEM simulations.…”
Section: Methodsmentioning
confidence: 99%
“…Several statistical models can be used for the statistical analysis of composites. According to Slah et al [ 27 ], experimental approaches are insufficient when testing and analyzing the wear behavior of composite materials. Those authors suggested that this approach should be complemented with FEM simulations.…”
Section: Methodsmentioning
confidence: 99%